2012
DOI: 10.3171/2012.6.jns111066
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in site-specific quality of life 6 months after endoscopic anterior skull base surgery: a prospective study

Abstract: Endoscopic skull base surgery is associated with an improvement in postoperative site-specific QOL as compared with the preoperative QOL. Short-term improvements are greater if gross-total resection is achieved. Sinonasal QOL transiently declines and then returns to preoperative baseline levels. Endoscopic skull base surgery is a valuable tool in the neurosurgical management of anterior skull base pathology, leading to improvements in site-specific QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
87
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(97 citation statements)
references
References 28 publications
(28 reference statements)
9
87
0
1
Order By: Relevance
“…Finally, McCoul and colleagues compared preoperative with postoperative SNOT-22 scores in a series of 66 patients and found a transient worsening at 3 weeks that returned to baseline values afterward. 28,29 Our data are consistent with these previous reports; no significant change in SNOT-22 scores was found > 9 months after surgery. These data indicate that long-term nasal function is as unchanged for extended craniopharyngioma surgery as it is for pituitary macroadenoma surgery.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Finally, McCoul and colleagues compared preoperative with postoperative SNOT-22 scores in a series of 66 patients and found a transient worsening at 3 weeks that returned to baseline values afterward. 28,29 Our data are consistent with these previous reports; no significant change in SNOT-22 scores was found > 9 months after surgery. These data indicate that long-term nasal function is as unchanged for extended craniopharyngioma surgery as it is for pituitary macroadenoma surgery.…”
Section: Discussionsupporting
confidence: 83%
“…McCoul et al recently showed that, in contrast to open surgery, endonasal endoscopic skull base surgery results in site-specific increases in QOL at 12 weeks and 6 months postoperatively compared with preoperative assessments; however, the majority of these cases were pituitary adenomas. 29 This study raised the possibility that minimally invasive endonasal endoscopic surgery may be better tolerated than open surgery with respect to QOL.…”
Section: Discussionmentioning
confidence: 99%
“…10,12,16,[19][20][21]23,25 These studies have at least 1 of several important limitations, including retrospective analysis of data, interpretation of unpaired postoperative data, use of nonvalidated outcome measures, and application of scales developed for other disease entities in unrelated patient populations. In this study, we sought to address the latter 2 limitations.…”
Section: Discussionmentioning
confidence: 99%
“…4,10,20,21 Current reports are limited by the use of QOL scales that either do not assess nasal complaints 13 or were not developed or validated for endonasal skull base surgery. 13,17,22 Furthermore, neurosurgeons should be familiar with the nasal morbidity of these techniques to aid in preoperative and postoperative patient counseling and to help place their approach-related morbidity in the context of open skull base techniques.…”
mentioning
confidence: 99%
“…Graham et al [17] compared the nasal symptoms in patients undergoing endoscopic or open surgery, noting that patients in the endoscopic surgery group had a lower score of nasal symptoms. Pant & McCoul et al [18,19] showed that the SNOT-22 scores and nasal symptoms increased moderately in the immediate postoperative period but subsequently returned to their preoperative values. Following the same line of study, Balaker et al [16] found that nasal symptoms were significantly improved over time but posterior rhinorrhea persisted in time until at least one year after surgery.…”
Section: Sinonasal Symptomsmentioning
confidence: 99%